High holding voltage SCRs with segmented layout for high‐robust ESD protection. Issue 18 (14th August 2017) - Huang, Xiaozong; Liu, Zhiwei; Liu, Fan; Liu, Jizhi; Song, Wenqiang
Abstract : Two high holding voltage silicon controlled rectifiers (SCRs) with segmented layout for high‐robust ESD protection are proposed, which are called SeSCR (segmented SCR) and anti‐SeSCR (anti‐segmented SCR), implemented in a 0.6 μm silicon on insulator (SOI) process. The transmission line pulse (TLP) characterisation results show that the holding voltage of the proposed structures can be elevated and adjusted with new layout topologies and different width of the segmentations for specific purposes. Meanwhile, the equivalent schematics and mechanisms of the segmented SCRs are also discussed.